Understanding Drivers of Ocular Fibrosis: Current and Future Therapeutic Perspectives - Fabiana Mallone (MDPI AG, 2021)
Ocular fibrosis leads to severe visual impairment and blindness worldwide, being a major area of unmet need in ophthalmology and medicine. To date, the only available treatments are antimetabolite drugs that have significant potentially blinding side effects, such as tissue damage and infection. There is thus an urgent need to identify novel targets to prevent/treat scarring and postsurgical fibrosis in the eye. In this review, the latest progress in biological mechanisms underlying ocular fibrosis are discussed. We also summarize the current knowledge on preclinical studies based on viral and non-viral gene therapy, as well as chemical inhibitors, for targeting TGFβ or downstream effectors in fibrotic disorders of the eye. Moreover, the role of angiogenetic and biomechanical factors in ocular fibrosis is discussed, focusing on related preclinical treatment approaches. Moreover, we describe available evidence on clinical studies investigating the use of therapies targeting TGFβ-dependent pathways, angiogenetic factors, and biomechanical factors, alone or in combination with other strategies, in ocular tissue fibrosis. Finally, the recent progress in cell-based therapies for treating fibrotic eye disorders is discussed. The increasing knowledge of these disorders in the eye and the promising results from testing of novel targeted therapies could offer viable perspectives for translation into clinical use.